(untitled) (Annals of Medical Research, 2024)
Aim: The anticancer effect of any Erica L. genus member has not yet been investigated. Hence, this study investigated the anticancer effect of Erica arborea, a high-level flavanone producer, in mouse breast cancer 67NR and 4T1 cells. Materials and Methods: Healthy mouse fibroblast L929, mouse primary breast cancer 67NR and mouse metastatic breast cancer 4T1 cells were treated with Erica arborea methanol and ethanol extracts to investigate the cellular toxicity, apoptosis, gene expression level and oxidative stress effect on cells. Results: According to our data, the methanol and ethanol extracts of Erica arborea caused apoptosis and G2/M cell cycle arrest. Also, the methanol and ethanol extracts of Erica arborea enhanced the level of reactive oxygen species (ROS), especially higher levels in mouse breast cancer 67NR and 4T1 cells, according to the healthy mouse fibroblast L929 cells. The treatment of the cells with Erica arborea extracts causes up-regulation of the pro-apoptotic Caspase-3, Caspase-9, Bax, and Bak genes and down-regulation of the anti-apoptotic Bcl-2 and Bcl-xL genes. Moreover, treatment with Erica arborea extract up-regulated the expression levels of cyclin-dependent kinase (CDK) inhibitor P21 and P27 genes while down-regulating the expression levels of cyclin B1 and cyclin A genes in cells. However, the mRNA expression level changes of these genes are significantly higher in breast cancer 67NR and 4T1 cells, according to the healthy mouse fibroblast L929 cells. Conclusion: The result of the present study indicated that Erica arborea stimulated apoptosis induction in mouse breast cancer 67NR and 4T1 cells, which was associated with G2/M cell cycle arrest by regulating the CDK signaling pathway through ROS generation.